Customer experience, retail banking division & financial performance evaluation (2010-2014) of BRAC Bank Limited - Hoque, Nabila (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.